2001
DOI: 10.1017/s037346330100145x
|View full text |Cite
|
Sign up to set email alerts
|

Infrasound and the Avian Navigational Map

Abstract: Birds can navigate accurately over hundreds to thousands of kilometres, and this ability of homing pigeons is the basis for a worldwide sport. Compass senses orient avian flight, but how birds determine their location in order to select the correct homeward bearing (map sense) remains a mystery. Also mysterious are rare disruptions of pigeon races in which most birds are substantially delayed and large numbers are lost. Here, it is shown that in four recent pigeon races in Europe and the northeastern USA the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 38 publications
(57 reference statements)
0
57
0
2
Order By: Relevance
“…True navigation implies that animals orient themselves by relying on cues available at the unfamiliar release site, and these usually are cues with a worldwide geographic distribution such as magnetic cues (Wiltschko and Wiltschko 1995;Lohmann 1991), lightdependent cues (Muheim et al 2006;Phillips et al 2010), infrasound cues (Hagstrum 2000), or odor cues (Jorge 2011;Wallraff 2005). In Experiment 3, we showed that adult L. pholis were able to orient themselves toward their home areas even if they were placed in an unfamiliar distant area, and they did so by relying on cues available in the unfamiliar area (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…True navigation implies that animals orient themselves by relying on cues available at the unfamiliar release site, and these usually are cues with a worldwide geographic distribution such as magnetic cues (Wiltschko and Wiltschko 1995;Lohmann 1991), lightdependent cues (Muheim et al 2006;Phillips et al 2010), infrasound cues (Hagstrum 2000), or odor cues (Jorge 2011;Wallraff 2005). In Experiment 3, we showed that adult L. pholis were able to orient themselves toward their home areas even if they were placed in an unfamiliar distant area, and they did so by relying on cues available in the unfamiliar area (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence does not support their use in this way, however, but rather indicates they act as a compass (Wallraff, 2005). Infrasound has been proposed to play a role in the navigation of homing pigeons (Hagstrum, 2000;Hagstrum, 2001), but so far only correlative evidence based on disturbance of orientation exists. The intensity and/or inclination of the Earth's magnetic field could be used to determine latitude (Phillips, 1996), and it has also been argued that the difference between magnetic (Phillips et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the Domestic Pigeon is selectively bred for longdistance flight and increased philopatry. Scientific studies have been mainly focused on determining which navigation strategies Domestic Pigeons use to return to their lofts (Wiltschko 1996, Hagstrum 2000, Holland et al 2000. Because Homing Pigeons seldom join Feral Pigeon populations, they contribute little to the formation of the Feral Pigeon gene pool (Haag 1998b).…”
mentioning
confidence: 99%